Analisis Perlakuan Akuntansi Aset Biologis pada Perusahaan Perkebunan: Tinjauan Keselarasan Antara PSAK 69 dan Konsep Dasar Teori Akuntansi - Witra Maison; Etsa Fahimah; Winda Yanti; Elvina Indriati; Disa Fide Kasoa (PENG: Jurnal Ekonomi dan Manajemen, 2026)
The implementation of PSAK 69, which is based on fair value, has introduced a new paradigm in the reporting of biological assets in Indonesia’s plantation sector; however, this has sparked in-depth discussion from the perspective of conceptual accounting theory. This study aims to analyze the accounting treatment of biological assets at Indonesian oil palm plantation companies and to evaluate the alignment of these practices with the structure and fundamental concepts of accounting theory. This study employs a descriptive qualitative method using a literature review approach and an analysis of the annual reports of PT Astra Agro Lestari Tbk and PT Salim Ivomas Pratama Tbk for the fiscal year 2025. The results show that both companies have applied fair value measurement for agricultural products in accordance with PSAK 69, using the discounted cash flow (DCF) model with discount rates ranging from 8.86% to 9.71% in SIMP. However, the objectivity of these estimates is challenged by the volatility of global commodity prices. In conclusion, the practice of recognizing and measuring biological assets based on fair value is highly relevant in reflecting current economic realities; however, it theoretically conflicts with the principles of historical cost and conservatism in basic accounting theory, as it results in significant volatility in non-cash earnings.